Transvaginal Ultrasonography and Saline Infusion Sonohysterography for the Detection of Intra-uterine Lesions in Pre- and Post-menopausal Women with Abnormal Uterine Bleeding - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2008)
This prospective study investigated 79 pre- and 25 post-menopausal women with abnormal uterine bleeding who underwent conventional transvaginal ultrasonography (TVS) and saline infusion sonohysterography (SIS) and compared the results with histopathological findings obtained by dilatation and curettage, hysteroscopy or hysterectomy. Histological examination revealed normal endometrial histology in 28 patients, intracavitary polyps in 46 patients, submucosal fibroids in 18 patients, intramural fibroids in six patients and endometrial hyperplasia in six patients. The sensitivity and specificity of TVS in detecting endometrial polyps were 65.2% and 87.9%, respectively, compared with 91.3% and 93.1% for SIS. The sensitivity and specificity of TVS in detecting uterine fibroids were 95.8% and 95.0%, respectively, versus 91.6% and 98.7% for SIS. These results show that SIS is a satisfactory method of identifying lesions and that it is easy and cost-effective, and improves on the diagnostic utility of TVS. SIS is also a less invasive alternative to hysteroscopy, so should result in less morbidity in the evaluation of abnormal uterine bleeding in women.
Keywords: ABNORMAL UTERINE BLEEDING; TRANSVAGINAL SONOGRAPHY; SALINE INFUSION SONOHYSTEROGRAPHY; INTRA-UTERINE LESIONS; CONTRAST SONOHYSTEROGRAPHY; DIAGNOSTIC HYSTEROSCOPY; ENDOMETRIAL ABNORMALITIES; PREMENOPAUSAL WOMEN; SONOGRAPHY; CAVITY; BIOPSY; HYSTEROSONOGRAPHY; ULTRASOUND; PATHOLOGY